2006
DOI: 10.1103/physrevlett.96.156104
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Structures and Recombination Pathways for Atomic Hydrogen on the Graphite (0001) Surface

Abstract: We present scanning tunneling microscopy results which reveal the existence of two distinct hydrogen dimer states on graphite basal planes. Density functional theory calculations allow us to identify the atomic structure of these states and to determine their recombination and desorption pathways. Direct recombination is only possible from one of the two dimer states. This results in increased stability of one dimer species and explains the puzzling double peak structure observed in temperature programmed deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
408
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(459 citation statements)
references
References 22 publications
50
408
1
Order By: Relevance
“…The previous experiment showed that some parts of the hydrogen adatoms desorb easily by annealing at room temperature, while some remaining parts can robustly survive a high-temperature heating. 2 From these results we understand that the observed stable clusters of hydrogen adatoms probably had features of the paired configurations.…”
Section: Unpaired Dimers Are Vulnerable To Desorptionmentioning
confidence: 63%
See 2 more Smart Citations
“…The previous experiment showed that some parts of the hydrogen adatoms desorb easily by annealing at room temperature, while some remaining parts can robustly survive a high-temperature heating. 2 From these results we understand that the observed stable clusters of hydrogen adatoms probably had features of the paired configurations.…”
Section: Unpaired Dimers Are Vulnerable To Desorptionmentioning
confidence: 63%
“…2 Another report suggested that a heat treatment at about 450 • C (24 hours in Ar atmosphere) is required for cleaning the hydrogenated graphene. 1 In this work, we showed that the migration barrier from the edge of the chairlike hydrogenated domain is about 2∼3 times higher than the desorption barrier from the unpaired configurations [ Figs.…”
Section: E Our Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculated value of hydrogen migration is smaller that achieved in previous calculations [5][6][7][8][9]. For verify used method and choice of technical parameters I have been performed calculations for different sizes of supercell.…”
Section: Migration Of Single Hydrogen and Hydroxyl Groups Without Watermentioning
confidence: 87%
“…Hydrogen adsorption on carbon based materials such as graphite and graphene is relevant to hydrogen storage, 9 band gap engineering, [10][11][12][13] and potentially as the first step in H 2 formation in the interstellar medium. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although there is enormous interest in H adsorption on carbonaceous surfaces, with graphene, graphite and polycyclic aromatic hydrocarbons (PAHs) being the most widely studied model systems, we still don't fully understand the seemingly simple process of how a single H atom adsorbs on the surface.…”
mentioning
confidence: 99%